A escola de educação básica da UFPB como organização aprendente: desafios docentes no contexto pandêmico - Mello, Cynthia Tribuzy Pereira de (2023)
This research aims to analyze the challenges and opportunities of teaching practice in the context of the COVID-19 pandemic within the UFPB School of Basic Education (DEBAS/CE/UFPB). This is a study of a qualitative nature, which reinforces the role of the school as a learning organization, capable of reviewing and changing behaviors, processes and functions, learning from its own experience, in constant dialogue with other areas of knowledge, taking on the challenges and errors as a substantial part of learning, in order to build a shared vision of the difficulties, possibilities, threats and strengths of teaching practice, which will allow modifying the organizational functioning of the school and anticipating strengthened future scenarios.Through bibliographic analysis and semi-structured interviews, it is intended to know the different pedagogical strategies used by EEBAS/UFPB teachers in conducting synchronous and asynchronous classes during the remote teaching period; identify the strengths and threats of the process of implementing remote teaching models in the territory of EEBAS/UFPB; present and reflect on the limits of virtuality as a school model and the paradoxes of present and future education. In the data analysis and interpretation of results, it is used analysis categories based on Ibero-American studies and research, in which communication tools will be analyzed; content and materials; control and follow-up; management and planning of the teaching-learning process of remote teaching, which will also culminate in the direction of innovative strategies to think about the paradoxes of present and future education, considering the great challenge of ensuring an inclusive, equitable and quality education, in line with with SDG 4 of the 2030 Agenda for Sustainable Development.